THE USE OF TRIZ (TIPS) METHODS FOR THE PERCEPTION OF THE MODERN VISUAL ART - Lagaeva, T. I.; Simak, A. I. (Art and Design, 2021)
The purpose of this investigation is the search and development of the methodological tools for the use of the Theory of Inventive Problem Solving (TRIZ/TIPS) for a deep and conscious perception of the modern visual arts by future artists and by professional painters in general. Methodology. The theoretical fundamentals of the research became the works of the researchers in the field of social-humanitarian sciences: culturology, art history, philosophy, semiotics. One can refer to the methodological basics the use of systemic, structural-semiotic and post-structural approaches. Results. In the process of the research, the differentiation, systematization and classification of methods of shaping in visual arts by adapting TRIZ methods was realized. The visual information for every TRIZ method was collected. As an example, we suggested a research abstract for the «Mediator» method, including a selection and the interpretation of the images, the analysis of method’s functions and their peculiarities, their specifics and resource possibilities. Scientific novelty. The scientific novelty consists in the fact that the authors have investigated the artistic works on the basis of adapted TRIZ methods, identified the variants of use of these methods and their functional meaning. Practical significance. The practical significance of the research consists in a deep analysis of semantic and esthetic components of the works of art, which can promote the enhancement of the artistic communication effectiveness and higher realization of the artists.